2013
DOI: 10.1095/biolreprod.113.111260
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in Candidate Genes Associated with Fertilizing Ability of Sperm and Subsequent Embryonic Development in Cattle1

Abstract: Fertilization and development of the preimplantation embryo is under genetic control. The present goal was to test 434 single nucleotide polymorphisms (SNPs) for association with genetic variation in fertilization and early embryonic development. The approach was to produce embryos from 93 bulls using in vitro procedures (n = 3-6 replicates per bull) and relate cleavage rate (CR) and development of cleaved embryos to the blastocyst stage (BDRC) to the genotype for each SNP. Bulls were selected to have either h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 56 publications
(84 reference statements)
2
49
0
1
Order By: Relevance
“…This 351 follows other studies in which single nucleotide polymorphisms and genome-wide methylation in 352 bulls were associated to embryonic development success [46,47]. We have to highlight that these 353 males were mostly undetected by the in vitro tests, therefore suggesting that we might combine our 354 laboratory tests with molecular analyses, in order to obtain a complete picture of semen fertility.…”
Section: Cryopreservation Of Semen 94supporting
confidence: 72%
“…This 351 follows other studies in which single nucleotide polymorphisms and genome-wide methylation in 352 bulls were associated to embryonic development success [46,47]. We have to highlight that these 353 males were mostly undetected by the in vitro tests, therefore suggesting that we might combine our 354 laboratory tests with molecular analyses, in order to obtain a complete picture of semen fertility.…”
Section: Cryopreservation Of Semen 94supporting
confidence: 72%
“…Using analyses of gene networks, candidate genes for cattle reproductive behavior have been identified (Kommadath et al 2011). A candidate gene approach has also been used to identify mutations in genes associated with fertilization and embryonic development during the pre-implantation period (Khatib et al 2009a,b;Cochran et al 2013a). Cochran et al (2013b) identified 51 SNPs in candidate genes that were associated with one or more fertility traits in Holstein bulls including DPR, cow conception rate (CCR) and heifer conception rate (HCR).…”
Section: Introductionmentioning
confidence: 99%
“…En particulier, des listes de SNP associés au nombre d'ovocytes viables, aux taux de fécondation, segmentation et développe-ment ont récemment été rapportés par plusieurs auteurs. Les effets maximaux observés entre les génotypes ont varié de 5,4 à 12,2 % pour les taux de fécondation (Khatib et al, 2009) et de 3,9 à 23,2 % pour le développement de l'embryon à partir de l'étape de segmentation (Cochran et al, 2013), démontrant ainsi l'intérêt potentiel la sélection génomique appliquée aux biotechnologies de l'embryon. Avec la puce LD (puce Illumina bovine LD; Illumina Inc., 5200 Illumina Way, San Diego, CA 92122 USA), une liste personnalisée de SNP pourrait être conçue afin de maximiser l'efficacité de la biotechnologie et de sélectionner les donneuses avec un potentiel maximal de production d'embryons.…”
Section: Nouveaux Caractères Permettant De Mieux Cibler Les Femellesunclassified